An anthropometric study to evaluate the correlation between the occlusal vertical dimension and length of the thumb - Basnet BB; Parajuli PK; Singh RK; Suwal P; Shrestha P; Baral D (Dove Medical Press, 2015)
Bishal Babu Basnet, Prakash Kumar Parajuli, Raj Kumar Singh, Pramita Suwal, Pragya Shrestha, Dharanidhar BaralDepartment of Prosthodontics, BP Koirala Institute of Health Sciences, Dharan, NepalBackground: Establishment of proper occlusal vertical dimension (OVD) is one of the important tasks for successful prosthodontic therapy. An ideal method for determining OVD in terms of cost, time, and instrument requirements has been sought in prosthodontics by various investigators. However, no such single method has been formulated. In the current anthropometric study, the relationship of the length of the thumb to the OVD was tested in two ethnic groups of Nepal, Aryans, and Mongoloids. The result of this study can be useful in determining proper OVD in edentulous patients.Aims and objectives: The primary aim of the present study was to evaluate the correlation between the length of the thumb and OVD in Aryan and Mongoloid ethnic groups. The secondary aim was to compare the correlation between OVD and other anatomic measurements (eye–ear distance and pupil-to-rima oris distance) in these ethnicities.Materials and methods: The OVD, thumb length, eye–ear distance and distance between pupil of eye and rima oris were measured in a total of 500 adult dentulous volunteers. The correlation between OVD and thumb length as well as other anatomic measurements was checked with Pearson's product moment correlation coefficient. Linear regression analysis was performed to determine the relationship of OVD to the length of the thumb.Results: The thumb length was significantly (P≤0.05) correlated with strong and positive values (Pearson’s coefficient =0.874 in the whole population, 0.826 in Aryans, and 0.944 in Mongoloids). Regression analysis showed that thumb length was significantly related to OVD in both ethnic groups.Conclusion: Within the limitations of the present study, the result implies that thumb length can be used as an adjunct for establishing OVD in the edentulous patients.Keywords: thumb, prosthodontic, caliper, rima oris, pupil of eye, edentulous patient